Calcium apatite and sodium alginate based composite material with ZnO microparticles doping - A. Turlybekuly; B.H. Shaimardanova; S.V. Plotnikov; A.D. Pogrebnjak; L.N. Yerokhina; G.K. Uazyrkhanova; A.V. Kasymbayev; E. Shaymardan; D.S. Dogadkin (Қарағанды университетінің хабаршысы. Физика сериясы)
Among the various materials for orthopedic use, hydroxyapatite (HA) is the most common material, due to its chemical similarity to bone. However, the application is limited because of low mechanical properties (especially high brittleness), low water solubility, low antimicrobial activity. The introduction of trace metal ions, as well as biopolymers, can improve its properties. The present work is devoted to the synthesis and complex study of bioactive material based on nanostructured hydroxyapatite with the addition of sodium alginate and ZnO, which has properties close to bone tissue. The article presents information on the method of preparation and the results of the investigation of a new composite material based on HA and sodium alginate with the addition of ZnO microcrystals. In the research work next methods were used: scanning electron microscopy with the possibility of energy-dispersion analysis, transmission electron microscopy and IR spectroscopy. The morphology, the particles phase statesare described, the regularities of the structural features of the new material are revealed. The main characteristics like, the ratio of Ca/P and functional groups correspond to the generally accepted parameters. An explanation of the grouping of ZnO microcrystals in the pores of the structure of a synthesized composite material is proposed.